(untitled) (Acta Scientiarum. Animal Sciences, 2026)
This study aimed to investigate the antioxidant and antibacterial properties of plant extracts derived from kiwi peels (Actinidia deliciosa), beet peels (Beta vulgaris L.), eggplant peels (Solanum melongena), and red cabbage leaves (Brassica oleracea L. var). Total phenols, flavonoids, free radical scavenging activity (DPPH), reducing power, and ferrous ion chelating capacity were evaluated. Beet peel extract showed the highest phenolic and flavonoid contents and exhibited the strongest DPPH scavenging activity, reaching 85% at 100 mg mL-1, as well as the most effective iron chelation, while eggplant peel showed the lowest activity. To assess preservative potential, kiwi and red cabbage extracts (0.5, 1, and 1.5%) were incorporated into minced meat patties inoculated with Listeria monocytogenes or stored as non-inoculated controls at 4 ± 1°C for 12 days. Microbiological analysis revealed significant reductions in total aerobic bacteria and L. monocytogenes counts, with kiwi peel extract showing the strongest inhibitory effect. Furthermore, treated patties demonstrated lower peroxide and free fatty acid values compared to controls (2.8 and 1.27 mEq kg-1, respectively, on day 12). These findings highlight the potential of selected plant extracts, particularly kiwi peels, as natural antioxidants and bio-preservatives in meat products.